MULTILINGUALISM AND LANGUAGE CONTACT IN THE POETIC WORLD OF ALEXANDER FAYNBERG - Abdumalikova Sevinch Tayirovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article explores the phenomena of multilingualism and language contact  within  the  poetic  corpus  of  Alexander  Faynberg.  As  a  prominent  Russian-speaking poet of Uzbekistan, Faynberg’s work serves as a unique linguistic intersection where Slavic syntactical structures meet Turkic cultural and conceptual frameworks. The study employs a contact-linguistic approach to analyze the integration of Uzbek loanwords, cultural realia, and "conceptual calques" into his Russian verses. Beyond mere lexical borrowing, the research investigates how this multilingual environment shapes the poet’s metaphorical system and stylistic identity. The findings suggest that Faynberg’s  "bilingual  consciousness"  creates  a  hybrid  poetic  space  that  facilitates intercultural  dialogue  and  reflects  the  complex  sociolinguistic  landscape  of  20th-century Central Asia. This study contributes to the field of transcultural linguistics by demonstrating how language contact can enrich poetic expression and foster a unified "National-Universal" aesthetic.